1971
DOI: 10.1530/jrf.0.0250393
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Dehydrogenase Isoenzymes in Rat Uterus: Changes During Pregnancy

Abstract: Total lactate dehydrogenase-specific activity and concentration of isoenzymes were determined on extracts of rat uterus at different stages of pregnancy, during the oestrous cycle and after ovariectomy.Total enzymatic activity increased during pregnancy. The rise was evident by the 5th day and continued steadily until the 14th day, when it attained maximal values. These high values were maintained up to the end of pregnancy and fell to the level of controls 4 days after parturition.The changes in enzyme activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…At phase IV the significantly low activity of M-isozymes in uterine fluid of parous women may be due to low levels of endogenous estrogen and to an antagonistic action of progesterone on estrogen induced LDH at this stage (Clark and Yochim 1971). This suggests that significantly high activity of M-isozymes in uterine fluid of parous women from early follicular phase to ovulatory phase (phase I to phase III) compared to that of infertiles, enables transformation of pyruvate into lactate (Battellino, Sabulsky and Blanco 1971), which is an important source of energy for the spermatozoa at this stage (Brinster 1967). Thus estrogen induced luminal M-isozymes enable the uterus to derive maximum energy from lactate in parous women which may help in vital reproductive processes.…”
Section: Discussionmentioning
confidence: 98%
“…At phase IV the significantly low activity of M-isozymes in uterine fluid of parous women may be due to low levels of endogenous estrogen and to an antagonistic action of progesterone on estrogen induced LDH at this stage (Clark and Yochim 1971). This suggests that significantly high activity of M-isozymes in uterine fluid of parous women from early follicular phase to ovulatory phase (phase I to phase III) compared to that of infertiles, enables transformation of pyruvate into lactate (Battellino, Sabulsky and Blanco 1971), which is an important source of energy for the spermatozoa at this stage (Brinster 1967). Thus estrogen induced luminal M-isozymes enable the uterus to derive maximum energy from lactate in parous women which may help in vital reproductive processes.…”
Section: Discussionmentioning
confidence: 98%
“…Hesseldeheer [30] observed a 50%-point increase in lactate dehydrogenase concentration in plasma after forcing pigs to exercise for 5 min, compared to a non-forced exercise group. Moreover, a rat study showed an increased e ciency of lactate dehydrogenase with increased level of muscle activities [31]. Challenging neonate piglets for 2 h at 10°C below their normal thermoneutral zone is considered as an extreme environmental condition which increases skeletal muscle shivering and, thereby also increase the lactate dehydrogenase concentration in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Rise in M-isozymes of LDH at DAM-i and DAM-2 also enables the uterus to transform pyruvate into lactate which is the only source of energy through glycolyte pathway during anaerobic condition (1) for the survival of male and female gametes in uterine lumen. Accumulation of lactate results in low oxygen tension when Misozymes of LDH dominate in the uterine fluid and thus initiates functioning of glycolytic pathway (2,4).…”
Section: Discussionmentioning
confidence: 99%